Sosiologi Keuangan: Dulu dan Kini - Achwan, Rochman (UI Scholars Hub, 2010)
Michael Power, a financial economist, asserts that amid the current global financial crisis what we required is a sociologist of finance. In history, the most important contributions of sociology of finance is to provide views of how people create and gave meaning to money and, vice versa, how people being made and constituted by money. In addition to being the engine of change towards modern civilization, money can also undermine and even destroy the fundaments of society. This paper provides a succinct review on the history of sociology of finance in an attempt to find its relevancy today.